Implementasi Program Nasional Pemberdayaan Masyarakat (Pnpm) Mandiri Pariwisata di Negeri Amahusu dan Latuhalat Kec. Nusaniwe Kota Ambon - Frety Matahelumual; Novita E. Kiljanin; Wiesje Ferdinandus (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research was conducted by Frety Matahelumual, Novita E. Kiljanin and Wiesje Ferdinandus with the title “Implementation of the National Tourism Empowerment Program (PNPM) in Amahusu and Latuhalat Kec. Nusaniwe Ambon City” was conducted to obtain a qualitative description of the implementation of the national community empowerment program that had been carried out. This study aims to determine the implementation process and benefits of the National Community Empowerment Program (PNPM) Mandiri Wisata as one of the empowerment programs in Ambon City. This study uses a qualitative approach at the research locus, namely the Amahusus country and the Latuhat country, the data analysis technique used in this study uses a qualitative descriptive model. The results of the study show that with this program, PNPM Mandiri Tourism in both tourist villages, namely the community can improve the family economy, create jobs and increase village income. Lack of communication and low human resources and budget resources so that the implementation process of the National Community Empowerment Program (PNPM) Mandiri Tourism has not been carried out optimally.